Critical Analysis on Tasawwuf Schools - Mokhamad Rohma Rozikin (Teosofia: Indonesian Journal of Islamic Mysticism, 2020)
As one of disciplines, Sufism has undergone the stages of scientific development. It is difficult to reach an agreement related to the classification of Sufism schools from the first time it appeared until today. However, by taking the characteristics of each thought into account, Sufism can be classified into several schools, namely Rajā 'wa khauf Sufism, Maḥabbah Sufism, Happy Sufism, Al-Ḥallāj Sufism, Al-Gazzālī Sufism, Philosophical Sufism, and Ibn Taimiyyah Sufism. Sufism that grew in the early days, in the first and second centuries of Hegira, such as Maḥabbah and Rajā' wa khauf Sufism, was in general undisputed because it was still far from the influence of foreign elements and had strong attachments to Al-Qur'an and Sunah. Sufism in the third and fourth centuries of Hijra, although from the scientific side is more established, systematic, and structured, the symptoms of conflict with Fiqh began to grow which reached its peak in the time of Al-Hallāj. Sufism in the fifth century, at the time of Al-Gazzālī, was the most beautiful period in the history of Sufism because Sufism and Fiqh could be integrated. Sufism in the next period began to had another conflict because of the influence of philosophy until the time of Ibn Taimiyyah who wanted to return Sufism to its origin. This paper conducted a literature review on the history of Sufism to capture the schools that have emerged since its inception. In the final section, a critical analysis of the Sufism schools was carried out and it was closed with a few ideas on how to eclectically adapt the results of this critical analysis for the Islamic Education learning.